Biofunctionalization of gold nanoshells monitored by surphase plasmon resonance - Ha Lien, Nghiem Thi; Do Thi Hue; Nguyen Thi My An; Do Quang Hoa; Nguyen Trong Nghia; Tran Hong Nhung (Vietnam Journal of Science and Technology, 2018)
Gold nanoshells were grown on monodispersed and aminopropyltriethoxysilane (APTES) functionalized silica nanoparticles cores with varying sizes ranging from 40-180 nm, which were prepared by Stober route. Gold shells were deposited onto the surface of silica NPs by using tetrakis(hydroxymethyl) phosphonium chloride and electroless gold plating method. The coverage of the gold nanoshells on the surfaces of the silica NPs was evaluated using surface plasmon resonance spectra and scanning electron microscope